Cross-Border Inequality between Indonesian Papua and Papua New Guinea: Causes and Solutions - Siborutorop, Jonathan (Universitas Cenderawasih, 2024)
This study examines the causes of cross-border inequality between border communities in Papua and South Papua provinces Indonesia and Sandaun and Western provinces of Papua New Guinea (PNG) through the lens of development theory and the concept of the developmental state. Using a qualitative-descriptive methodology, this study posits that the inequality existing between Indonesian and Papua New Guinean border communities is caused by the large investment and state capacity committed by the Indonesian government in developing its border communities compared to the Papua New Guinean government’s lack of economic investment and state capacity in developing its peripheral border regions. Furthermore, this study suggests that this existing inequality can be solved by encouraging state capacity building and investment in border communities in partnership with the private sector in the Papua New Guinean side of the border.